The Usability of Mobile Experiment Application in Science Subject for Secondary Student - Anis Amilah (Journal of Advanced Research in Computing and Applications, 2023)
Conducting experiment can help to increase our knowledge of the subject or concept learned. During experiment, the concept learned need to be applied in order to solve the problem. From applying the concept in experiment, the concept can be further applied in real life. The problems of conducting experiment is some of the teacher might not able to guide them out of school hours, the student does not know how to practice the theory learned in class in the experiment and student did not focus or give full attention to the details in experiment book whether it is because they did not aware of the content or too lazy to read it. In order to replace book used during the experiment, mobile phones emerge as the suitable medium for the replacement. Because of technological awareness among all people and technological advancement had increasing recently, most students now had their own mobile phone. Therefore, mobile phone as a medium of learning seems reasonable. In order to make the learning process on mobile phone more interesting, gamification and game-based learning technique are applied on the application. Gamification and game-based learning technique can help in making learning more fun and challenging. Based on the testing conducted, most student agreed that uses of mobile application as a new learning medium had potential to replace the current learning medium which is using book. For the improvement in the future, the limitation on application need to be overcome and the topic and uses of multimedia element will be further improve to make the learning process more interactive.